Why do primigravidae request caesarean section in a normal pregnancy? A qualitative study in Iran - Ibrahim, Faisal; Nasrin, Matinnia; Abdul Rahman, Hejar; Khodakarami, Z. (Elsevier, 2014)
Objective To gain a deeper understanding of why Iranian primigravidae request caesarean section without any medical indication. Design Qualitative study. Data were gathered through semi-structured interviews, and thematic analysis was undertaken. Setting Four health care centres at Hamadan University of Medical Sciences, Hamadan, Iran. Participants 14 primigravidae who requested caesarean section without any medical indication. Findings Reasons for requesting caesarean section were related to fear of childbirth (labour pain, injury to mother or infant), complications after vaginal delivery (vaginal prolapse, urinary incontinence, sexual dysfunction), trust in obstetricians, and lack of trust in maternity ward staff. Key conclusions and implications for practice The main reasons given for requesting caesarean section show that there is urgent need for effective antenatal assessment to enable pregnant women to ask questions and express their concerns. In order to promote vaginal birth, there is a need to develop antenatal education and strategies to enhance women's knowledge, confidence and competence about vaginal birth. Health care providers should be re-educated about the observance of medical ethics and professional rules in their practices, and change their attitudes and behaviours to vaginal birth. Evaluation, improvement and change in maternity care policies are recommended to promote natural childbirth.